GAME BASED LEARNING SEBAGAI SALAH SATU SOLUSI DAN INOVASI PEMBELAJARAN BAGI GENERASI DIGITAL NATIVE - Natalis Sukma Permana (Lembaga Penelitian STKIP Widya Yuwana, 2022)
This paper aims to describe game based learning as one of the learning innovations for digital natives. In this paper, the author uses a literature study approach by reading several sources about digital native and game based learning. For digital natives who were born in the digital era, it is very easy to adapt to technology. Digital natives expect something creative and innovative. Of course this needs to be seen by the teacher as a necessity as well as an opportunity in developing learning activities. One of the reasons why learning is designed to be game-based is because digital natives like competition, rewards, fun and fast-paced activities. So, game based learning is one of the solutions for the development of learning in the digital era. In developing game-based learning, what teachers need to pay attention to is the ultimate goal of learning. In implementing game-based learning, teachers can take advantage of digital applications with educational nuances such as educandy, kahoot, quiziz, and wordwall